Readmissions after endoscopic skull base surgery: associated risk factors and prevention. Issue 1 (7th October 2019) - Vengerovich, Gennadiy; Park, Ki Wan; Antoury, Layal; Wells, Christine; Suh, Jeffrey D.; Lee, Jivianne T.; Heaney, Anthony P.; Bergsneider, Marvin; Wang, Marilene B.
Abstract : Background: Unplanned readmissions within 30 days of discharge is a quality measure introduced by the Centers for Medicare Services. This measure has been used to rate hospital quality and also to penalize hospitals for excess readmissions. It has been hypothesized that shorter hospital stays and fewer readmissions are associated with endoscopic skull base procedures. In this study we analyze endoscopic skull base procedures performed at our institution over a 10‐year period to identify rates and factors associated with readmissions after endoscopic skull base surgery. Methods: A retrospective chart review was performed at a tertiary care academic medical center identifying patients who underwent endoscopic skull base surgery over the past 10 years. Data on patient demographics and tumor variables, as well as patient variables such as body mass index (BMI), revision surgery, history of skull base radiation, medical comorbidities, intraoperative cerebrospinal fluid (CSF) leaks, and postoperative CSF leaks, were recorded. Results: Eight hundred thirty‐three patients were included in our study. Sixty‐one patients (7.3%) were readmitted a total of 66 times within 30 days. The most common reasons were as follows: hyponatremia (n = 18); CSF leak (n = 17); epistaxis (n = 3); diabetes insipidus (n = 3); rhinorrhea (n = 3); as well as other reasons. Statistical analysis revealed that the presence of intraoperative CSF leak was the only statistically significant variable associated with increased rate of readmissions within 30 days of discharge ( p < 0.001). Conclusion: Presence of intraoperative CSF leak was the only statistically significant variable associated with an increased risk for readmission after surgery. Other tumor and patient variables were not associated with an increased risk of readmission within 30 days.